Phase Transitions, Crystal Structures, and Magnetic Properties of Ferrocenium Ionic Plastic Crystals with CF3BF3 and Other Anions. Issue 4 (29th January 2019) - Kimata, Hironori; Sakurai, Takahiro; Ohta, Hitoshi; Mochida, Tomoyuki
Abstract: Salts of cationic sandwich complexes often exhibit an ionic plastic phase; however, only a few exhibit a plastic phase at room temperature. To explore the use of the CF3 BF3 anion to lower the transition temperature to the plastic phase, we prepared salts of CF3 BF3 with various ferrocene derivatives, [D][CF3 BF3 ] (D=FeCp*2, Fe(C5 Me4 H)2, Fe(C5 H4 Me)2, FeCp(C5 H4 Me), FeCp2 ; Cp*=C5 Me5, Cp=C5 H5 ). Although [FeCp*2 ][CF3 BF3 ] exhibited a plastic phase above 417 K, the other salts formed room‐temperature ionic plastic crystals with a phase transition to the plastic phase in the range 266–291 K. The crystal structure and thermal properties of [FeCp2 ][OTf] were elucidated for comparison. In addition, decamethylferrocenium salts with other anions were synthesized and structurally characterized: [FeCp*2 ][X] (X=N(SO2 F)2 and B(CN)4 ) exhibited a phase transition to the plastic phase above 400 K, whereas carborane‐containing salts [FeCp*2 ]2 [B12 F12 ] and [FeCp*2 ][Co(C2 B9 H11 )2 ] did not exhibit a plastic phase. Abstract : Phase transitions, crystal structures, and magnetic properties of salts of ferrocene derivatives with CF3 BF3 − and other anions were investigated. Most of the CF3 BF3 salts exhibited a plastic phase at room temperature.